Mother & Myth in Spanish Novels : Rewriting the Matriarchal Archetype. - Schumm, Sandra (Bucknell University Press, 2011)
Remembering the forgotten mother is a major theme in Myth & Mother in Spanish Novels and reflects the current interest in the recuperation of historic memory in Spain. The novels in this study feature mature protagonists who recall their mothers as a way to define their own identities and to nullify the fictional matricide prevalent in post-war Spanish novels; this twenty-first-century fiction highlights the haunting presence of the mother and begs comparison with myth.